2020
DOI: 10.3390/antiox9100924
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of HO-1 and Autophagy in the Protective Effect of Magnolol in Hepatic Steatosis-Induced NLRP3 Inflammasome Activation In Vivo and In Vitro

Abstract: Magnolol (MG) is the main active compound of Magnolia officinalis and exerts a wide range of biological activities. In this study, we investigated the effects of MG using tyloxapol (Tylo)-induced (200 mg/kg, i.p.) hyperlipidemia in rats and palmitic acid (PA)-stimulated (0.3 mM) HepG2 cells. Our results showed that Tylo injection significantly increased plasma levels of triglyceride and cholesterol as well as superoxide anion in the livers, whereas MG pretreatment reversed these changes. MG reduced hepatic lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…In this mouse experiment, we also found that one antioxidant enzyme, HO-1, responded to the increase in palmitic acid levels in the blood. This feature was reproduced in the liver of mice fed an HFD, and consistent with several reports that discuss the importance of HO-1 in other mouse models of fatty livers [ 25 , 26 , 27 , 28 ]. Therefore, to further investigate the relationship between HO-1 and oxidative stress, we performed experiments using HepG2 cells with palmitate exposure.…”
Section: Discussionsupporting
confidence: 90%
“…In this mouse experiment, we also found that one antioxidant enzyme, HO-1, responded to the increase in palmitic acid levels in the blood. This feature was reproduced in the liver of mice fed an HFD, and consistent with several reports that discuss the importance of HO-1 in other mouse models of fatty livers [ 25 , 26 , 27 , 28 ]. Therefore, to further investigate the relationship between HO-1 and oxidative stress, we performed experiments using HepG2 cells with palmitate exposure.…”
Section: Discussionsupporting
confidence: 90%
“…The mechanism of bioactive compounds such as phenols, carotenoids, alkaloids, or sulfur to activate the Nrf2- Keap1 pathway was either through the direct induction of Nrf2 expression or through inhibition of the dimerization of Nrf2 and Keap1 or enhancement of the transcriptional activity of Nrf2 ( Fakhri et al, 2020 ). MAG, known as an antioxidant, has been shown to stimulate the expression of Nrf2 and HO-1 in hepatocytes and hepatic steatosis mice ( Kuo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of HSP70 has been reported to protect against HS-induced organ damage, which is associated with the activation of the autophagic process [9,30]. On the other hand, recent studies have revealed that regulation of the autophagy pathway is novel anti-inflammatory targets of HO-1 [12,42]. By induction of autophagy, HO-1 protects against hepatocyte cell death and liver injury from infection/ sepsis in mice [43].…”
Section: Discussionmentioning
confidence: 99%